Biogas Production from Water Hyacinth (Eichhornia Crassipes): The Effect of F/M Ratio. (May 2018) - Nugraha, W D; Syafrudin,; Pradita, L L; Matin, H H A; Budiyono,
Abstract: Distribution of water hyacinth (Eichhornia crassipes), generally considered as a water weed, that has been a problem which can harm the environment, irrigation system, and agriculture. However water hyacinth can be used in biogas production because it has large enough amount of hemicellulose contents. The purpose of this study was to know the effect of F/M ratio to biogas production from water hyacinth waste with Liquid Anaerobic Digestion (LAD) method. A series of laboratory experiments using biodigester were performed in batch anaerobic operation at room temperature. F/M ratio that used in each reactor was 39.76, 20.03, 13.32, and 10.01. Degradation process was done in 60 days. The result showed that F/M ratio effects to the biogas production. The best performance of biogas production from this research will be obtained if F/M ratio is in the range of 10.01-20.03 (correspond to 25%-50% of rumen fluid) with water hyacinth as the main substrate.